Penilaian Kinerja dan Kebutuhan Pelatihan serta Pengembangan Karyawan - Qori’ah, Anik Rotul (Lembaga Yasin AlSys, 2025)
This study aims to examine the methods used in employee performance appraisal, identify training and employee development needs, and determine the benefits of training and development for employees at PT. PLN (Persero) Udiklat Pandaan or UPDL Pandaan. The evaluation results show that measuring the effectiveness of programs and their impact on employee performance can enhance future training programs and ensure that employee development aligns with the company's objectives. Based on these results, PT. PLN (Persero) Udiklat Pandaan or UPDL Pandaan is committed to continuously improving the quality of human resources in the Distribution and Commerce fields through objective performance evaluations and training programs tailored to the needs of employees and the company. The implementation at PT. PLN (Persero) Udiklat Pandaan or UPDL Pandaan provides comprehensive training facilities and programs for employees. The training utilizes diverse methods, including lectures, discussions, demonstrations, case studies, games, role-playing, business simulations, e-learning, on-the-job training, off-the-job training, on-the-job development, action learning, experiential learning, and motivational learning. These programs aim to enhance employee competencies in carrying out tasks in the DMI field. This study highlights the importance of performance appraisal, training needs, and employee development to support the sustainable development of human resources.